A catalogue of white dwarfs in Gaia EDR3. Issue 3 (22nd September 2021) - Gentile Fusillo, N P; Tremblay, P-E; Cukanovaite, E; Vorontseva, A; Lallement, R; Hollands, M; Gänsicke, B T; Burdge, K B; McCleery, J; Jordan, S
ABSTRACT: We present a catalogue of white dwarf candidates selected from Gaia Early Data Release 3 (EDR3). We applied several selection criteria in absolute magnitude, colour, and Gaia quality flags to remove objects with unreliable measurements while preserving most stars compatible with the white dwarf locus in the Hertzsprung–Russell diagram. We then used a sample of over 30 000 spectroscopically confirmed white dwarfs and contaminants from the Sloan Digital Sky Survey (SDSS) to map the distribution of these objects in the Gaia absolute magnitude–colour space. Finally, we adopt the same method presented in our previous work on Gaia Data Release 2 (DR2) to calculate a probability of being a white dwarf ( P WD ) for ≃1.3 million sources that passed our quality selection. The P WD values can be used to select a sample of ${\simeq} 359\, 000$ high-confidence white dwarf candidates. We calculated stellar parameters (effective temperature, surface gravity, and mass) for all these stars by fitting Gaia astrometry and photometry with synthetic pure-H, pure-He, and mixed H–He atmospheric models. We estimate an upper limit of 93 per cent for the overall completeness of our catalogue for white dwarfs with G ≤ 20 mag and effective temperature ( T eff ) > 7000 K, at high Galactic latitudes (| b | > 20°). Alongside the main catalogue we include a reduced proper motion extension containing ${\simeq} 10\, 200$ white dwarf candidates with unreliable parallax measurements that could, however, be identified on the basis of their proper motion. We also performed a cross-match of our catalogues with SDSS Data Release 16 (DR16) spectroscopy and provide spectral classification based on visual inspection for all resulting matches.